Employment and labor regulation: Evidence from manufacturing firms in Bolivia, 1988 - 2007 - Beatriz Muriel; Carlos Gustavo Machicado (Institute for Advanced Development Studies (INESAD), 2012)
This paper analyzes employment in Bolivian registered manufacturing firms during 1988 to 2007, establishing its relationship with labor regulation. Estimating job flows, we find that firms with high temporary worker rates (less labor regulation costs) are those with both higher job reallocation rates and higher net employment growth, and only they contributed to employment growth during the country economic downturn, 1998-1999. In addition, estimating demand functions, we find the following effects of recent changes in labor norms: i) the compulsory basic salary rise in 2006-2009 entailed costs in terms of job losses, 5.6 percent for production workers and 4.8 percent for non-production workers; iii) the major labor costs derived from the new pension law, enacted in 2010, decreased employment demand around 1 percent; and, iv) labor protection policies decreased production workers demand.
Keywords: D24; J01; J23; K31; 330; job flows; labor demand; labor regulation; translog function; unbalanced panel; Industrielle Beschäftigung; Arbeitsmarktpolitik; Bolivien